Passeriformes: nest predators and prey in a Neotropical Savannah in Central Brazil - França, Leonardo Fernandes (2009)
The identification of predators of birds' nests, crucial to a better understanding of predator-prey interactions, remains poorly known. Here we provide evidence that birds, and especially passerines, may depredate birds' nests in the Cerrado (Neotropical Savannah) of Central Brazil. Data was collected primarily in a Conservation Unit (Estação Ecológica de Águas Emendadas) during the breeding season, between 2003 and 2007. We report and discuss details on 14 events of nest predation, 12 of which by passerines, mostly by curl-crested jays - Cyanocorax cristatellus (Temminck, 1823). The results of our study suggest that the role of birds as nest predators in the Cerrado has been underestimated and needs to be further investigated.